Mother–Child Reminiscing About Emotionally Negative Events and Children’s Long-Term Mental Health - Koh, Jessie Bee Kim; Wang, Qi (Frontiers in Psychology, 2021)
The present study examined the longitudinal relation between mother-child reminiscing of emotionally negative events and children’s mental health. European-American and Chinese-American mothers discussed with their 4.5-year old children an event that was emotionally negative to the child. At age 7, children’s mental health was assessed, including measures for externalizing problems, internalizing problems, negative social self (an Asian-salient dimension of depression), behavioral problems, and socially adaptive behavior. Independent of culture, maternal reference to negative emotional terms was related to fewer externalizing, internalizing, and behavior problems in children, maternal attribution of emotions to children was associated with lower negative social self in children, maternal explanation of children’s emotions was linked to fewer externalizing problems and lower negative social self in children, and maternal reconfirmation of the explanations was related to fewer externalizing and behavioral problems in children. In contrast, maternal attribution of emotions to other people was associated with more externalizing problems and higher negative social self in children of both cultures. Some important cultural differences emerged. Chinese-American mothers’ mention of negative emotional terms was linked to lower negative social self in children, and Chinese-American mothers’ reconfirmation of explanation was related to more socially adaptive behaviors in children. No such relations were found in the European-American sample. The findings underscore the importance of family emotional reminiscing for children’s long-term well-being and the role of culture in shaping the process.